Konsep Makna Syifā’ dalam Wacana Tafsir Sufi - Heryanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Qur'an uses the word al-Syifā' to refer the meaning of treatment, not using the term al-Ṭibb which is more synonymous with treatment based on instructions from the hadith. The Qur'an and the hadith basically have the same position in discussing treatment, namely both as a source of knowledge to treat various diseases, both physical and non-physical. This study will question the meaning of the Sufis on the concept of Shifā' in the Qur'an. The study will be directed to find out how the concept of the meaning of Syifā' is in Sufi interpretations. This research is part of library research whose data is taken from library sources. The data source used in this research is a list of authors of Sufi commentaries that have been clarified by Al-Zahabi in the book Tafsīr wa al-Mufassirūn. This study uses a thematic model approach by taking into account aspects of the meaning of Syifā' terminology in the Qur'an. The results show that in interpreting the word Syifā', the Sufis tend to prioritize the metaphysical aspects. Their interpretation of the meaning of Shifā' is converging on an understanding of spiritual dimension remedies whose orientation is to treat the human heart. Almost all of the verses that are interpreted are always associated with medicines that have an inner dimension, such as medicine to cleanse the soul of all the evil that surrounds it, such as, medicine for longing for Allah, for overcoming doubts, for being able to be tawadu' and to always closer to Allah.